Bili so izkoriščeni - Simikič, Alenka (Etnolog. Nova vrsta (Ljubljana), 2001)
The article presents the memories of 1941-1945 war period as told by four people and is illustrated with documentary and pictorial material. The first story is that of Emil Hostnik from Gaj who lived through the war as an exile on the big property of a resettled Romanian Germanč the second one comprises apart of the life story of Veronika Hostnik, née Derganc, from Ponikve, who now lives in Gaj, and who exiled worked as a forced labourer in a bomber factory in Kassel. The third story is that of Tone Bukovinski, born in Koritno, who today lives in Velika Dolina. He was a prisoner of war in Germanyand survived to see the end of the war as a Royal Guard in Belgrade. The fourth life story is that of Ludvik Kren, born in Stara cerkev in the Kočevje region, who was forced to settle in Cerklje ob Krki; during the war he was a teacher in Velika Dolina and his story is also that of the Kren family.
Keywords: izgnanci; prisilno delo; spomini; življenske zgodbe; druga svetovna vojna; World War II; Slovenia; Slovenija